ANALISIS KOMPARATIF PELAYANAN AKADEMIK PADA FAKULTAS EKONOMI DAN FAKULTAS ISIP UNIVERSITAS JENDERAL ACHMAD YANI - Roslina, Nita Yura; Manik, Ester (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
Upgrading of skills as well as knowledge to make a new generation of high quality to be able to pursue and develop science and technology are regarded as a catalyst of economic progress that will improve people’s welfare. Therefore, the college has an ethical responsibility to the quality of its graduates as work ability, creativity, community recognition as an absorber of human resources towards credibility. Private universities are faced with tight competition and should do anticipate to explore and improve all aspects of service that are owned, including in terms of academic services. Academic services can be interpreted as an attempt by the college to provide facilities to meet the needs of students in matters related to academic activities. This study aims to find out, observe, assess and analyze whether there are significant differences anatara academic services students of the Faculty of Economics and the Faculty of Social and Political Sciences University General Achmad Yani. In this study took a sample of 149 students of the Faculty of Economics and 143 students from the Faculty of Social and Political Sciences Unjani.The method of analysis used to answer the hypothesis is to use parametric statistics that comparative analysis with t test (t-test). The results of his research is the average score of students of the Faculty of Economics Unjani to attribute academic services at 73.7% (relatively high) compared to the average score of students of the Faculty of Social and Political Sciences of the attributes of academic services amounted to 72.6% (high enough). The difference score of 1.2% illustrate the difference. Results of calculation with the formula t-test separated sample variance relation is independent (uncorrelated) and the second variant sample is not homogeneous, known F count larger than F table (1.3> 1,271). Based on calculations by comparing t arithmetic with t table known that t t table amounted to -1.79 -0.7047 with a standard error of 7.5% (0.075), thus there are significant differences on the attributes of academic services between the students of the Faculty of Economics with the students of the Faculty of Social Sciences and Political University General Achmad Yani. Keywords : comparative anaysis, academic serivices.